2017
DOI: 10.1126/science.aan2735
|View full text |Cite
|
Sign up to set email alerts
|

Tuning quantum nonlocal effects in graphene plasmonics

Abstract: The response of an electron system to electromagnetic fields with sharp spatial variations is strongly dependent on quantum electronic properties, even in ambient conditions, but difficult to access experimentally. We use propagating graphene plasmons, together with an engineered dielectric-metallic environment, to probe the graphene electron liquid and unveil its detailed electronic response at short wavelengths. The near-field imaging experiments reveal a parameter-free match with the full theoretical quantu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
353
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 319 publications
(375 citation statements)
references
References 50 publications
6
353
0
2
Order By: Relevance
“…The combination of graphene with two-dimensional (2D) insulators-such as hexagonal Boron Nitride (hBN)-has allowed an unprecedented control of the distance that a 2D material can be placed in the vicinity of metallic films or nanostructures. In fact, the placement of a graphene sheet at a distance of a few nanometers away from a metal surface has recently been experimentally demonstrated [9], in a similar setting as depicted in Fig. 1.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…The combination of graphene with two-dimensional (2D) insulators-such as hexagonal Boron Nitride (hBN)-has allowed an unprecedented control of the distance that a 2D material can be placed in the vicinity of metallic films or nanostructures. In fact, the placement of a graphene sheet at a distance of a few nanometers away from a metal surface has recently been experimentally demonstrated [9], in a similar setting as depicted in Fig. 1.…”
Section: Introductionmentioning
confidence: 87%
“…This is possible due to the interplay of graphene plasmons and the screening exerted by the nearby metal film. This approach has revealed that the nonlocal properties of graphene's conductivity have to be included in a proper account of the experimental data [9,37]. In graphene, it is more useful to describe the nonlocal response via the material's nonlocal dynamical conductivity, which within linear-response theory relates the surface current, K s (r,ω), and the in-plane electric field, E (r,ω), via [3] …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have assumed a local form for ε , ignoring the fact that at very short distances this assumption breaks down (12,13,14) which will remove the possibility of a perfect singularity as postulated here. Systems also have resistive loss as we have discussed and to some extent the two effects compensate for one another: non locality by removing the perfect singularity will tend to produce a discrete spectrum; on the other hand loss will smear a discrete but still dense spectrum into a continuum leaving the broad band absorption intact.…”
Section: /Pagementioning
confidence: 99%